Pengaruh kepuasan dan motivasi kerja terhadap kinerja karyawan Bank Central Asia Pekanbaru - Tantra, Fidella; Hendriani, Susi; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted at Bank Central Asia KCU Pekanbaru. The purpose of this study was to examine the influence of work motivation and job satisfaction of the employees ' performance and also to find out whether there is a shared influence motivation and job satisfaction of employees of Bank Central Asia performance KCU Pekanbaru. The variables used are motivation and job satisfaction as the independent variable and the dependent variable as employee performance. The populations in this study are all employees of Bank Central Asia remain KCU Pekanbaru. Up to the year 2013 employees remain in Bank Central Asia KCU Soweto was 119 people and everything will be made as a sample, so the method of data collection is done with Sampling Purposive to all employees of Bank Central Asia KCU Pekanbaru. Methods of data analysis used were multiple linear regressions using SPSS version 17.Based on the results from study and discussion of the mind that the motivation and job satisfaction the significant effect of simultaneous performance of Bank Central Asia KCU Pekanbaru (F Test). Motivation and job satisfaction are also influential in partial Performance of Bank Central Asia KCU Pekanbaru (t-test). This indicates that all the independent variables examined have significant influence both partially or the dependent variable with respect to simultaneous.Keywords: Work Motivation, job satisfaction and Employee Performance